Prevalence and severity levels of post-radical prostatectomy incontinence: different assessment instruments - Luciana Regina Ferreira da Mata; Cissa Azevedo; Lívia Cristina de Resende Izidoro; Darkiane Fernandes Ferreira; Fabrícia Eduarda Baia Estevam; Fabrícia Moreira Amorim Amaral; Tânia Couto Machado Chianca (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze urinary incontinence prevalence and severity in prostatectomized men assessed by three different instruments. Methods: a cross-sectional study was conducted with 152 men. The pad test, pad used, and International Consultation on Incontinence Questionnaire - Short Form (self-report) were considered. Data were analyzed using Spearman's correlation, Kappa index, considering a significance level of 0.05. Results: urinary incontinence prevalence was 41.4%, 46.7% and 80.3% according to pad used, pad test and self-report. Positive correlations and moderate to poor agreement were found between the instruments. As for severity, most participants had mild incontinence. The largest number of cases of mild and severe incontinence was identified by self-report. Conclusions: the self-report showed higher values for prevalence of mild and severe severity levels. Through the identified differences, we propose that the objective assessment (pad used and pad test) be associated with individuals' perception (self-report) to better estimate prevalence and severity.